0959 Evening Chronotypes Mediate The Association Between Early Life Stress And Emotion Dysregulation In Bipolar Disorder: A Pilot Study. (27th April 2018) - Cipollone, G; Paolilli, F L; Novi, M; Masci, I; Caruso, D; Moretto, U; Palagini, L
Abstract: Introduction: In Bipolar Disorder, both circadian rhythms and emotion dysregulation play an important role by negatively influencing its trajectory. In addition many studies documented an association of negative life events and Bipolar Disorder onset and course. The aim was to assess the association between early life stress, chronotypes and emotion regulation in this mood disorder. Methods: Fifty two: patients (39 females, 47.6 ± 13.1 years) with a Bipolar Disorder- I depressive episode with mixed features, according to DSM-5 and 20 healthy controls (15 females, 47.7 ± 12 years) were recruited. Subjects were evaluated with the SCID-DSM-5 and Morningness Eveningness Questionnaire (MEQ), Difficulties in Emotion Regulation Scale (DERS), Beck Depression Inventory (BDI-II), Mania Rating Scale (MRS) and Early Trauma Inventory-Short Form (ETISR-SF). An a priori power analysis, regression and mediation analyses have been performed. Results: In bipolars the MEQ score was 49.2 ± 7.1, with 16 subjects (31%) showing evening chronotypes, and in healthy controls was 58.2 ± 1.5, with 3 (15%) showing evening types (p<0.05). In bipolars the BDI-II and MRS scores were respectively 23 ± 11.2 and 8.9 ± 6.0 while it was 5.2 ± 1.2 and 3.0 ± 0.1 in healthy subjects (p<0.001); ETISR-SF score was respectively 7.1 ± 04 and 2.1 ± 1 (p<0.01). In bipolars the greater early life stress significantly correlated with greater MEQ scores (coeff= -0.16, p=0.03), MEQ evening types (coeff= 1.1 p=0.04), higher BDI-II and MRS scores (p=0.01, p=0.03) and greater DERS scores (coeff= 0.7, p=0.01). Considering BDI-II and MRS as covariates, greater early life stress independently predicted evening chronotypes (coeff= 0.14, p=0.04) and greater emotion dysregulation (coeff= 1.8, p=0.005), particularly difficulties engaging in goal-directed behaviors (coeff= 0.43, p=0.005). Evening chronotypes mediated the association between early life stress and emotion dysregulation (Z=2.7, p=0.03). Conclusion: Early life stress may impact on later psychopathology, especially favoring both circadian sleep rhythms and emotion dysregulation. Particularly if, in bipolars, evening chronotypes may contribute to the association between early life stress and emotion dysregulation, we may hypothesized early life stress having negative consequences at first on chronobiological rhythms. Further studies with longitudinal design are required. Support (If Any): no support